(untitled) (Journal of Enam Medical College, 2012)
At both the national and community level, cancer registration schemes are central to research into the nature and causation of cancer, to the planning of health service resources and cancer control programmes, and to the assessment of their efficacy. Cancer registration is thus a part of the modern health information system. There are two major types of cancer registries -hospital-based registries and population-based registries. It is of paramount importance that the issue of development of cancer registry in developing countries should be taken into account. Although, the cancer registry system in Bangladesh is in infantile stage, it should be the aim of the health planner of our country to develop population-based cancer registry as early as possible. The extra difficulties and expenses involved are certainly outweighed by the enhanced validity and usefulness of the data generated. DOI: http://dx.doi.org/10.3329/jemc.v1i2.11467 J Enam Med Col 2011; 1(2): 76-80